Lung Function and Respiratory Symptoms of Petrol Station Attendants in Central and North Jakarta and Its Contributing Factors - Putri Suci Ramadhany; Faisal Yunus; Agus Dwi Susanto (Respiratory Science, 2020)
Background: To satisfy growing needs of petrol consumption in big city many new petrol stations has been built. Petrol station attendant is considered to have high risk exposure to dangerous pollutant from motor vehicle emission and petrol fumes, especially while filling up petrol tanks. Combination of those exhaust and petrol fumes is suspected to cause the reduction of lung function. Methods: This research is a cross sectional study in petrol station in Central Jakarta and North Jakarta region between August 2017 and February 2018. A total of 97 petrol station attendants were taken in this research using consecutive sampling technique. The subjects were interviewed with questionnaires, spirometry and chest radiograph. Measurements of sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), ozone (O3), particulate matter 2,5 (PM 2,5) and steam gasoline (benzene) concentrations were performed at the study sites. Results: In this study, 56.7% normal spirometry results, 42.3% abnormalities in the form of restriction, 1% obstruction and none of which experienced mixed disorders of restriction and obstruction. Most subjects (84.6%) did not experience respiratory complaints, 10.3% had a dry cough and 5.1% complained of cough with phlegm. There was a statistically significant association between peak expiratory flow and duration of work (p=0.011), but no significant association with other parameters such as forced vital capacity (FVC), %FVC, forced expiratory volume in the first second (FEV1), %FEV1 and the ratio of FEV1/FVC. Conclusion: Prevalence of lung function abnormalities of petrol station attendant is 43,3% and respiratory symptoms at 15,4% subject.